Spider silk : evolution and 400 million years of spinning, waiting, snagging, and mating - Brunetta, Leslie, 1960- (Yale University Press, 2010)
"The orb web, that iconic wheel-shaped web most of us associate with spiders, contains at least four different silk proteins, each performing a different function and all meshing together to create a fly-catching machine that has amazed and inspired humans through the ages. Brunetta and Craig tell the intriguing story of how spiders evolved over 400 million years to add new silks and new uses for silk to their survival "toolkit" and, in the telling, take readers far beyond the orb. The authors describe the trials and triumphs of spiders as they use silk to negotiate an ever-changing environment, and they show how natural selection acts at the genetic level and as individuals struggle for survival."